2001
DOI: 10.1111/j.1651-2227.2001.tb00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability in children: variation with age and reliability in the diagnosis of cow's milk allergy

Abstract: Kalach N, Rocchiccioli F, de Boissieu D, Benhamou PH, Dupont C. Intestinal permeability in children: variation with age and reliability in the diagnosis of cow's milk allergy. Acta Paediatr 2001; 90: 499-504. Stockholm. ISSN 0803-5253 Objective: To analyse to what extent age may alter intestinal permeability (IP) in children and to assess its reliability according to clinical manifestations in cow's milk allergy (CMA). Design: A routine prospective study was performed in 200 children (12.5 § 23 mo, 0.5-168… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
0
12
1
1
Order By: Relevance
“…16,17 While gut permeability drops rapidly during the first days of life, a very gradual process of gut closure is observed over the first few years of life. 18,19 It is currently unknown whether this second phase of prolonged, but diminished gut permeability has a significant physiologic role. Studies measuring intestinal permeability by lactulose/mannitol ratio have shown prolonged intestinal permeability in formula-fed infants compared to breastfed infants during the first 2 weeks, 14,20 with similar gut permeability observed at 1 month.…”
Section: (Re)defining Neonatal Gut Closurementioning
confidence: 99%
“…16,17 While gut permeability drops rapidly during the first days of life, a very gradual process of gut closure is observed over the first few years of life. 18,19 It is currently unknown whether this second phase of prolonged, but diminished gut permeability has a significant physiologic role. Studies measuring intestinal permeability by lactulose/mannitol ratio have shown prolonged intestinal permeability in formula-fed infants compared to breastfed infants during the first 2 weeks, 14,20 with similar gut permeability observed at 1 month.…”
Section: (Re)defining Neonatal Gut Closurementioning
confidence: 99%
“…Clinical features due to IgE-mediated reactions are expressed as immediate symptoms mostly. Clinical symptoms may involve the skin, respiratory tract and gastrointestinal tract and can even lead to a systemic anaphylactic reaction (Kalach et al, 2001;Furrie, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we demonstrated to the best of our knowledge, for the first time, the effect of bilirubin on the intestinal barrier of healthy term newborns before phototherapy. SAT is widely considered a reliable nontoxic, noninvasive and simple to perform test to study the intestinal barrier (10). Lactulose permeates the intestinal barrier by the paracellular route through paracellular junctions while mannitol uptake occurs preferentially through the transcellular route (11).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, UCB may alter lipid polarity and fluidity, protein order and redox status (20) thus impairing the transcellular diffusion of mannitol. This explanation, however, may be too naive as no significant intestinal epithelial injury or decreased absorptive capacity has ever been shown in animal (or in vitro) studies in Gunn rats (9,10). Moreover, the evidence of an exclusively transcellular permeation of monosaccharides is still controversial.…”
Section: Discussionmentioning
confidence: 99%